2019
DOI: 10.1103/physrevlett.122.057207
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Field-Induced Spin Gap in an S=1/2 Chiral Staggered Chain

Abstract: We investigate the low-temperature magnetic properties of the molecule-based chiral spin chain [Cu(pym)(H2O)4]SiF6·H2O (pym = pyrimidine). Electron-spin resonance, magnetometry and heat capacity measurements reveal the presence of staggered g tensors, a rich low-temperature excitation spectrum, a staggered susceptibility and a spin gap that opens on the application of a magnetic field. These phenomena are reminiscent of those previously observed in non-chiral staggered chains, which are explicable within the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…This suggests that spinons can be viewed as quantum solitons [24] and therefore exhibit chirality, which was indeed confirmed by polarized neutron scattering [25]. Soliton and breather modes were identified in neutron-scattering [26,27] and electron-spin-resonance [28,29] experiments.…”
Section: Introductionmentioning
confidence: 63%
“…This suggests that spinons can be viewed as quantum solitons [24] and therefore exhibit chirality, which was indeed confirmed by polarized neutron scattering [25]. Soliton and breather modes were identified in neutron-scattering [26,27] and electron-spin-resonance [28,29] experiments.…”
Section: Introductionmentioning
confidence: 63%
“…In terms of physically realising such systems, the use of organic ligands has proven highly effective in constructing crystal architectures that readily promote lowdimensional magnetic behaviour [12][13][14][15][16]. A selection of recently published materials showcase the ability to test the limits of the theoretical understanding of S = 1/2 and S = 1 chain materials [17][18][19]. To achieve quasi-onedimensional (Q1D) behaviour, the choice of intrachain bridging-ligand is a decisive one, as it ultimately determines the sign and strength of the intrachain exchange interaction (J).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment [16] on [Cu(pym)(H 2 O) 4 ]SiF 6 · H 2 O found that ESR peaks of this compound exhibit unconventional power-law dependence on the magnetic field. A part of this unconventional behavior is attributed to the chiral rotation and the complex dependence of the coupling constant on the magnetic field.…”
Section: Uniform Dm Interactionmentioning
confidence: 99%
“…h 0 and h 2 are applied in the x and the y directions, respectively. The model used in Ref [16]. contains a weak XXZ interaction and the uniform DM interaction.…”
mentioning
confidence: 99%